Effect of platform switching on bone loss around implants: a retrospective study - Alexandrino, Lorena Gonçalves (2024)
Introduction: The impact of switching platform unevenness on bone stability is not yet known. Objective: The aim of this study was to evaluate the effect of different mismatching of platform switching on the bone stability around implants with a Morse taper with internal angulation of 16º after 4-11 months of prosthetic loading. Material and method: The implants were evaluated in two experimental periods (implant installation time and loading, and maintenance visit – after between 4 and 11 months of prosthetic loading). The variables evaluated were the bone level assessed by periapical radiography, and the survival rates of the dental implants. The peri-implant bone level was also evaluated according to the diameter of the implants used. Result: One hundred and nineteen dental implants placed in 45 patients were evaluated. Of these implants, 33 presented a 3.5mm diameter, 33 a 3.75mm diameter, 19 a 4.0 mm diameter, and 34 a 4.3 mm diameter. The variation in bone loss from these implants was 0.36 ± 0.34 mm. The correlation index between the implant diameters and peri implant bone loss was r = 0.01, with a p value = 0.22. This finding indicates that the correlation between the variation in peri-implant bone level and the implant diameter was not significant. The survival rate of the total sample was 97.47%. Conclusion: Implants with a Morse taper connection and 16º internal angulation presented good early survival rates with limited bone loss, that was not influenced by the degree of platform switching.